Eleven novel polymorphic microsatellite DNA markers from the green-lipped mussel, Perna viridis. - Ong, C. C.; Teh, C. H.; Tan, Soon Guan; Yusoff, Khatijah; Yap, Chee Kong (Pleiades Publishing, Inc., 2008)
We report on the characterization of 11 polymorphic microsatellite loci in P. viridis, the first set of such markers developed and characterized for this species. The number of alleles per locus ranged from 2 to 7, whereas the observed heterozygosity ranged from 0.0447 to 0.4837. These markers should prove useful as powerful genetic markers for this species.